Old English poetic diction not in Old English verse or prose – and the curious case of Aldhelm's five athletes. (26th November 2014) - Griffith, Mark
Abstract: Three contexts characterized by the occasional appearance of Old English poetic diction outside of Old English poetry — debased verse, rhythmical prose, and prose passages with rhetorical heightening — have been surveyed by previous scholars, but no serious consideration has been given to the use of poetic lexis to be found in the surviving glosses and glossaries. The article first looks at some examples in these non-poetic texts of poetic words used as markers of the heroic, the elegiac, the sublime, the exotic and the monstrous, before moving on to a detailed analysis of a significant discovery. The glosses and glossary batches to Aldhelm's extended simile in De Virginitate comparing the educational development of Christian nuns to the exertions of various athletes display (when taken together) a unique cluster of poetic diction, comparable in density (and perhaps also in motivation) to that found only in the most enriched passages of traditional heroic poetry.